Clinical features and long term outcome of epilepsy in periventricular nodular heterotopia. Simple compared with plus forms. Issue 6 (14th May 2004) - d'Orsi, G; Tinuper, P; Bisulli, F; Zaniboni, A; Bernardi, B; Rubboli, G; Riva, R; Michelucci, R; Volpi, L; Tassinari, C A; Baruzzi, A
Abstract : Objectives: Little is known about the long term outcome of patients with periventricular nodular heterotopia (PNH) and epilepsy, particularly the course of seizures. This study investigated the electroclinical and prognostic features of 16 patients with PNH. Methods: Of 120 patients with epilepsy and malformations of cortical development, 16 had PNH. Of these, eight patients had periventricular nodules only (simple PNH) and eight also presented with other cortical or cerebral malformations (subcortical heterotopia; polymicrogyria; focal dysplasia; schizencephaly; cortical infolding; agenesis of the corpus callosum; mega cisterna magna and cerebellar atrophy) (PNH plus). All patients underwent clinical, neurophysiological, and MRI investigation. The mean follow up was 17.3 years (2–40 years). Results: Two electroclinical patterns emerged: (1) The first pattern, associated with simple PNH, was characterised by normal intelligence and seizures, usually partial, which began during the second decade of life. The seizures never became frequent and tended to disappear or become very rare. The EEG showed focal abnormalities. (2) The second pattern, associated with PNH plus, was characterised by mental retardation and seizures that began during the first decade of life. The seizures were very frequent in most cases and sudden drops were observed in six patients. Seizures were medically refractory in four patients. The EEG showed focal and bisynchronous abnormalities. Conclusions: Two groups of PNH patients with different electroclinical and neuroradiological features can be identified after a long term follow up. The presence of other types of cortical or cerebral malformations, in addition to periventricular nodules, determines a poor prognosis.